Optimalisasi Penegakan Hukum terhadap Pengendara yang Menghindari Tilang: Upaya Mewujudkan Efektivitas dan Kepatuhan Berlalu Lintas - Bella Pertiwi (Consensus : Jurnal Ilmu Hukum, 2025)
Effective law enforcement is a key factor in fostering traffic discipline and reducing violations on the roads. However, the phenomenon of drivers attempting to evade ticketing, either by fleeing or resisting law enforcement, remains a significant challenge in traffic law enforcement efforts. This article aims to analyze strategies and measures that can be implemented to optimize law enforcement against drivers who avoid fines. Through a more systematic approach and supporting technologies, such as the implementation of automated monitoring systems and improving the capacity of law enforcement officers, it is hoped that a stronger deterrent effect can be created, resulting in improved driver compliance with traffic regulations. This study also discusses the importance of community involvement in supporting these policies to create a safer and more orderly traffic environment. In conclusion, strengthening law enforcement against drivers who evade fines can significantly contribute to enhancing traffic compliance and reducing road accidents.